Conformation change of hornet silk proteins in the solid phase in response to external stimulation. Issue 5 (31st January 2018) - Kuroda, Reiko; Kameda, Tsunenori
Abstract: Hornet silks adopt a variety of morphology such as fibers, sponge, films, and gels depending on the preparation methods. We have studied the conformation change of hornet silk proteins ( Vespa mandarina ) as regenerated films, using chiroptical spectrophotometer universal chiroptical spectrophotometer 1, which can measure true circular dichroism spectra without artifact signals that are intrinsic to solid‐state samples. The spectra showed that the proteins in films alter the conformation rapidly from the α‐helix to the coiled coil and then to a β‐sheet structure in response to heat/moisture treatment, but the transformation stopped at the coiled coil state when the sample was soaked in EtOH/water solution. Water is required for the α‐helix to the coiled coil transition, and extra energy is required for the further transition to a β‐sheet structure. This is the first successful circular dichroism study of fibril silk proteins to follow the conformation changes in the solid state. This work shows that proteins can undergo conformational changes easily even in the solid phase in response to external stimuli, and this can be traced by solid‐phase‐feasible chiroptical spectrophotometers. Application of unnatural stress to proteins gives valuable insights into their structure and characteristics. Abstract : Hornet silks adopt a variety of morphology such as fibers, sponge, films, and gels depending on the preparation methods. We have shown that by using a special chiroptical spectrophotometer that can remove erroneous signals from macroscopic anisotropies of solid samples, universal chiroptical spectrophotometer 1, the proteins change the secondary structure easily in the solid state in response to external stimulation (eg, steam), from α‐helix to coiled coil and then to β‐sheet.